A Gāthic Rite? A Critique of the Cosmological Interpretation of the Gāthās I. Issue 2 (4th March 2017) - Ahmadi, Amir
Abstract : In the last few decades ritual interpretation of the Gāthās has replaced the biblical one as the dominant paradigm. The emphasis on the central role of ritual in the Avesta is well justified. This realization has given rise to the question of the role and meaning of ritual in the Gāthās. Marijan Molé had tried to argue that the Gāthās in fact describe and accompany a rite whose purpose was the preservation/renovation of the cosmic order. Students of the Gāthās working within the new paradigm have taken up Molé's general frame. They have tried to show that the Gāthās, collectively or individually, is the text of a particular rite that served, among others, to preserve the cosmic order, especially the daily rise of the sun. The article questions the validity of this thesis. Its focus is on the version of the thesis we find in a number of recent publications by Jean Kellens. He tries to show that the first Gāthā (Ahunauuaitī) describes a unitary pre-dawn ritual that comprised a haoma rite and an animal sacrifice, and had cosmological and eschatological pretensions. His textual analyses and arguments are examined in some detail. The article concludes that Kellens's attempt must be deemed unsuccessful.